Suspension culture of human mast cells/basophils from umbilical cord blood mononuclear cells. - Ogawa, M (1983)
Selective growth of human mast cells/basophils was obtained in suspension cultures of mononuclear cells from umbilical cord blood. A fraction of culture supernatant of phytohemagglutinin-stimulated T cells, which lacked interleukin 2, was required for the selective growth of mast cells. When the mononuclear cells were cultured for 2-4 wk in the presence of the fraction, 50-90% of the total cells in the cultures contained metachromatic granules. Under the optimal culture conditions, the number of mast cells/basophils recovered from the cultures was 30-60% of the number of mononuclear cells plated. Cultured mast cells/basophils bear 1.2-3.83 X 10(5) IgE receptors per cell and contained 0.48-1.6 micrograms of histamine per 10(6) cells. The average forward rate constant, k1, and dissociation constant, k-1, for the binding of human IgE to IgE receptors on the cells were 1.9 X 10(5) M-1 sec-1 and 6.9 X 10(-5) sec-1, respectively (average equilibrium constant = 2.75 X 10(9) M-1). Specific binding of human IgE with high affinity indicates that the cells recovered in the suspension culture are human mast cells/basophils. Cultured cells sensitized with human IgE released a substantial amount of histamine upon exposure to anti-IgE. The results indicate that human mast cells/basophils obtained in the culture are functionally mature.